Simulation of CO-H2-Air Turbulent Nonpremixed Flame Using the Eddy Dissipation Concept Model with Lookup Table Approach - Kazui Fukumoto; Yoshifumi Ogami (Journal of Combustion)
We present a new combustion simulation technique based on a lookup table approach. In the proposed technique, a flow solver extracts the reaction rates from the look-up table using the mixture fraction, progress variable, and reaction time. Look-up table building and combustion simulation are carried out simultaneously. The reaction rates of the chemical species are recorded in the look-up table according to the mixture fraction, progress variable, and time scale of the reaction. Once the reaction rates are recorded, a direct integration to solve the chemical equations becomes unnecessary; thus, the time for computing the reaction rates is shortened. The proposed technique is applied to an eddy dissipation concept (EDC) model and it is validated through a simulation of a CO-H2-air nonpremixed flame. The results obtained by using the proposed technique are compared with experimental and computational data obtained by using the EDC model with direct integration. Good agreement between our method and the EDC model and the experimental data was found. Moreover, the computation time for the proposed technique is approximately 99.2% lower than that of the EDC model with direct integration.